Uswah Hasanah Learning Model and its Implementation in Learning Islamic Religious Education: Model Pembelajaran Uswah Hasanah Dan Implementasinya Dalam Pembelajaran Pendidikan Agama Islam - Wahidi, Rosid; Syahidin, Syahidin (Civilization Research: Journal of Islamic Studies, 2024)
Education based on the values of holy Qur'an has an important role to advance the quality of education. But now, the reality of education shows us the condition of students is apprehensive. Apart from being messy about moral standpoint, they also had difficulty following Islamic Religious Education learning. Based on these problems, learning models that can accommodate the development of good character and support IRE learning are urgently needed. Therefore the researcher then tried to conduct this research with the aim that the researcher could provide references and describe the concept of the uswah hasanah model and its application in IRE learning. In this study, researchers used qualitative approach with literature study method. The results of the research show’s four important points about the application of the uswah hasanah model in IRE learning. Like believing in the concept of uswah hasanah, realizing Rasulullah as a representative of uswah hasanah, understanding the psychological basis of uswah hasanah, know the types of exemplary in the Qur'an, and paying attention to the linkages of uswah hasanah in IRE learning.